2000
DOI: 10.1089/thy.2000.10.471
|View full text |Cite
|
Sign up to set email alerts
|

A Novel V59E Missense Mutation in the Sodium Iodide Symporter Gene in a Family with Iodide Transport Defect

Abstract: Iodide transport defect results from the malfunction of iodide transporter (sodium iodide symporter [NIS]), and is characterized by low uptake of iodide into thyroid cells. Genetic analysis revealed that a T354P missense mutation causes iodide transport defect in the homozygous state and is a frequent mutation in the Japanese population. We recently reported three siblings with iodide transport defect harboring the T354P mutation in the heterozygous state. Here we report a novel V59E missense mutation associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The length of the identified protein (618 amino acids) is identical to that of rNIS but is smaller than hNIS (643 amino acids). Several residues with a potential importance for the function and/or the stability of the protein (Pohlenz & Refetoff 1999, Fujiwara et al 2000, as well as glycosylation (Levy et al 1998) and potential phosphorylation sites (Dai et al 1996, Smanik et al 1996 present in rNIS and hNIS are conserved in the mNIS sequence (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the identified protein (618 amino acids) is identical to that of rNIS but is smaller than hNIS (643 amino acids). Several residues with a potential importance for the function and/or the stability of the protein (Pohlenz & Refetoff 1999, Fujiwara et al 2000, as well as glycosylation (Levy et al 1998) and potential phosphorylation sites (Dai et al 1996, Smanik et al 1996 present in rNIS and hNIS are conserved in the mNIS sequence (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the three N-linked glycosylation sites (Asn225, 485 and 497), the potential cAMP phosphorylation site (549-KRSS-552) and the two protein kinase C (PKC) phosphorylation sites at position 548-TKR-550 and 593-TKK-595 found in the mNIS protein were also localised at equivalent position in the rNIS protein. Finally, four residues of hNIS or rNIS (Gly93, Gln267, Thr354 and Gly538), in positions corresponding to identified point mutations which result in thyroid iodide transport defects and congenital hypothyroidism in the human (Pohlenz & Refetoff 1999, Fujiwara et al 2000, are also conserved in the mouse protein. These data indicate that the isolated sequence is the mNIS orthologue of rNIS and hNIS.…”
Section: Identification Of a Cdna From Mouse Mammary Gland Highly Hommentioning
confidence: 99%
“…The resulting impairment in I − uptake in the thyroid leads to congenital hypothyroidism, which, unless treated early in life by TH administration, causes goiter and even mental retardation. Study of the 14 ITD-causing NIS mutations identified to date (27)(28)(29)(30)(31)(32)(33)(34)(35)(36) has been instrumental in the identification of residues key for NIS transport activity (5, 16, 17, 22-25, 37, 38). For example, the analysis of T354P revealed the role in NIS function of TMS9, where this mutation is located (23).…”
Section: Significancementioning
confidence: 99%
“…The NIS is predicted to have a serpentine structure with 13 transmembrane domains with an amino-terminus facing the extracellular milieu and an intracellular carboxyl terminus facing the cytosol (7). To date, several loss-of-function mutations of the NIS gene and two deletions (19,20) have been described in patients with ITD (10)(11)(12)(13)(14)(15)(16)(17)(18). In this article, we describe a new homozygous deletion of two amino acids in the NIS protein in a patient with CH having the complete clinical picture of ITD.…”
Section: Introductionmentioning
confidence: 95%